(untitled) - Clark, Ed (New York, 2004)
Researchers in business and organizational studies discuss conducting field work in countries that are assumed to be transforming from socialist to capitalist. They suggest that such work requires special qualities, that existing methodologies pay too little attention to personal and social experiences, that personal and social difficulties are more likely to arise than in more normal societies, and that researchers in other disciplines can learn from their experience. They do not report research findings.
Keywords: Social sciences,Social sciences,Social sciences,Post-communism,Post-communism; Research,case studies,Field work,Case studies,Case studies; Europe, Eastern,Europe, Central,Europe, Eastern,Europe, Central